Towards a Complexity Framework for Transformative Evaluation - Robert Picciotto (The Evaluation Center at Western Michigan University, 2020)
Background:  Complexity ideas originating in mathematics and the natural sciences have begun to inform evaluation practice. A new wave in evaluation history is about to break. A new mindset, new methods, and new evaluation processes are being summoned to explore and address the challenges of global pandemics, growing inequities, and existential environmental risks. This is part of a broader paradigm shift underway in science where interdisciplinarity has become the norm rather than the exception. Purpose: This article explores the utility of a complexity framework for a more effective evaluation function. It unearths the antecedents of complexity thinking; explores its relevance to evolving knowledge paradigms; provides a bird's eye view of complexity concepts; uses the logic of complex adaptive systems to unpack the role of evaluation in society; and draws the implications of contemporary social challenges for evaluation policy directions. Setting: Not applicable. Intervention: Not applicable. Research design: Not applicable. Findings: The evaluation complexity challenge coincides with an urgent imperative: social transformation. The on-going pandemic has brought to light the disproportionate effects of health emergencies on disadvantaged groups and emphasized the urgency of improving the interface between humans and nature. It has also demonstrated the importance of modelling for policy making - as well as its limitations. Evaluation, a complex adaptive system, should be transformed to serve society. Keywords: complexity; computers; disciplines; emergence; modelling; paradigm, systems